Mastication induces long-term increases in blood perfusion of the trigeminal principal nucleus. (17th December 2015) - Viggiano, A.; Manara, R.; Conforti, R.; Paccone, A.; Secondulfo, C.; Lorusso, L.; Sbordone, L.; Di Salle, F.; Monda, M.; Tedeschi, G.; Esposito, F.
Highlights: 3D-ASL MRI allows measurement of brain perfusion before and after mastication. Perfusion MRI reveals increased blood flow in the trigeminal system after mastication. Chewing consuetude affects vascular tones in the trigeminal principal nucleus. Abstract: Understanding mechanisms for vessel tone regulation within the trigeminal nuclei is of great interest because some headache syndromes are due to dysregulation of such mechanisms. Previous experiments on animal models suggest that mastication may alter neuron metabolism and blood supply in these nuclei. To investigate this hypothesis in humans, arterial spin-labeling magnetic resonance imaging (MRI) was used to measure blood perfusion within the principal trigeminal nucleus (Vp) and in the dorsolateral-midbrain (DM, including the mesencephalic trigeminal nucleus) in healthy volunteers, before and immediately after a mastication exercise consisting of chewing a gum on one side of the mouth for 1 h at 1 bite/s. The side preference for masticating was evaluated with a chewing test and the volume of the masseter muscle was measured on T1-weighted MRI scans. The results demonstrated that the mastication exercise caused a perfusion increase within the Vp, but not in the DM. This change was correlated to the preference score for the side where the exercise took place. Moreover, the basal Vp perfusion was correlated to the masseter volume. These results indicate that the local vascular tone of the trigeminal nuclei can be constitutively altered by the chewing practice and by strong or sustained chewing.